Risk Factors for Gout Arthritis in the Coastal Area of Wapunto Community Health Center: a Review - Wa Ode Fatima; Sitti Suslyanti Sanwar (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Arthritis is a musculoskeletal disorder characterized by joint inflammation, which can result in pain, stiffness, swelling, and restricted mobility. This condition significantly affects the quality of life, particularly when left inadequately managed. In Indonesia, the prevalence of arthritis has shown an increasing trend in line with the aging population and lifestyle changes, including in rural and coastal regions. Objective: This study aims to examine the factors influencing the incidence of gout arthritis in coastal communities. Methods: A Systematic Literature Review (SLR) approach was employed to identify and analyze 34 relevant scientific articles from international publications. Articles were retrieved from the Google Scholar database, covering the publication period from 2020 to 2025. Results: Seventeen articles met the inclusion criteria and were subjected to further analysis. These studies identified various etiological factors and management strategies for gout arthritis that are particularly relevant to coastal settings. Conclusion: The occurrence of gout arthritis in coastal communities is not solely an individual health concern but also reflects broader structural issues related to socio-economic conditions and limited access to healthcare services. Addressing this problem requires comprehensive policy interventions, including public health education, early detection initiatives, improvement of occupational conditions, and expanded access to medical services, in order to reduce prevalence and enhance the well-being of coastal populations. Keywords: Arthritis, Coastal Areas, Gout Arthritis, Elderly